Case Report: SVF after chemoradiotherapy for cervical cancer diagnosed by non-contact hysteroscopic technique - Sun, Xuemei; He, Yinghua; Yang, Xuedong; Wu, Yu; Yang, Yanhuan; Wang, Yanping; Fan, Xiuhua (Frontiers in Medicine, 2025)
Sigmoidovaginal fistula (SVF) is an extremely distressing and complex condition that significantly impacts a patient’s quality of life. The successful management of SVF relies on accurately identifying the fistula’s location and tract. However, preoperative localization can be challenging in certain cases. In this report, we describe a rare complication in a patient with stage IVA cervical cancer who developed SVF after concurrent chemoradiotherapy. Conventional diagnostic methods, including electron colonoscopy, methylene blue testing, and fistulography, were unable to locate the fistula. As an alternative, we used a non-contact hysteroscopic technique, which successfully identified the location, size, and number of fistulas. This method is particularly effective for patients with SVF, especially in postmenopausal women with narrowed or adherent vaginal tracts, women with intact hymen, and those with complex, high-grade vaginal fistulas resulting from cancer treatment with chemoradiotherapy.